Building a Golden Generation: Synergy of Education, Technology, and Qur'anic Values - Yuni Herdiyanti; Miftakul Janah; Roni Susanto (LP3M Pascasarjana STAI Ibnurusyd, 2025)
The development of the golden generation is a strategic agenda in forming individuals who excel intellectually, morally, and spiritually. The synergy between education, technology, and Qur'anic values ​​is a key element in creating a generation that is not only academically intelligent, but also has a strong character. This article explores the role of education as the main foundation in developing human resources, technology as an accelerator in the learning process, and Qur'anic values ​​as moral and ethical guidelines in life. With a multidisciplinary approach, this study highlights the integration of these three aspects in creating a golden generation that is able to face global challenges. The results of the study show that technology-based education based on Qur'anic values ​​is able to improve the quality of character and competence of students.